Pemblokiran Rekening Oleh Bank Secara Sepihak - Sopamena, Ronald Fadly (Bacarita Law Journal, 2022)
There are times when the bank blocks the customer's account so that the customer cannot access the money stored in the bank. This will certainly harm the customer because his money is unilaterally detained by the bank. This writing aims to discuss legal aspects and protection for customers against unilateral blocking by banks. The research method used in this research is normative juridical or what is known as legal research which is carried out by reviewing and analyzing the substance of legislation on the subject matter or legal issue in its consistency with existing legal principles. Blocking of customer accounts can be done based on the request of law enforcement if the funds are suspected to be the result of a crime. Blocking of a customer's account can also be done if the account holds assets belonging to customers who are declared bankrupt so that the curator has the authority to secure the assets. Customers who are harmed due to unilateral account blocking by the bank can take dispute resolution either outside the court or through the court.